Determinasi Kepuasan Kerja terhadap Disiplin Kerja Karyawan: Studi Literatur pada Konteks Manajemen Sumber Daya Manusia - Yusuf Effendi; Agung Safitri; Fadhilla Washilla; Eti Hadiati; Junaidah (SAKALIMA: Pilar Pemberdayaan Masyarakat Pendidikan, 2026)
This study aims to analyze the determination of job satisfaction on employee work discipline within the context of Human Resource Management (HRM) through a literature review approach. The background of this study is based on the importance of job satisfaction as a psychological factor influencing employee work behavior, particularly in shaping sustainable work discipline, while previous studies have tended to be partial and predominantly quantitative in approach. The research method employs a descriptive qualitative design using a literature review approach, involving the identification, selection, and synthesis of relevant scientific sources from both accredited national journals and reputable international publications. The findings indicate that job satisfaction plays a significant role as a determinant of employee work discipline, reflected in dimensions such as satisfaction with the job itself, compensation, interpersonal relationships, and supervision, and further strengthened by contextual factors such as organizational culture, leadership, and reward systems. The discussion emphasizes that the relationship between job satisfaction and work discipline is multidimensional and dynamic, where job satisfaction not only serves as an outcome of organizational policies but also functions as a key antecedent in shaping disciplined behavior. This study concludes that enhancing job satisfaction is a crucial strategy for strengthening employee work discipline in a sustainable manner. The implications of this study suggest the need for organizations to develop human resource management policies oriented toward improving job satisfaction as a strategic effort to enhance work discipline, as well as encouraging future research to empirically test this conceptual model across various organizational contexts.